2012
DOI: 10.1039/c2ja30179b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selenium by X-ray fluorescence spectrometry using dispersive solid-phase microextraction with multiwalled carbon nanotubes as solid sorbent

Abstract: A dispersive solid-phase microextraction (DSPME) with multiwalled carbon nanotubes (MWCNTs) as solid sorbent and ammonium pyrrolidinedithiocarbamate (APDC) as chelating agent was developed for determination of selenium. In the proposed procedure, the Se(IV)-APDC complex is adsorbed on MWCNTs dispersed in aqueous samples. After the adsorption process, the aqueous samples are filtered and MWCNTs with selenium chelate are collected onto a filter. The loaded filters are directly measured using X-ray fluorescence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 29 publications
(54 reference statements)
0
25
1
Order By: Relevance
“…The comparative results are summarised in Table 5. The analytical figures of merit obtained revealed that the SDSPME/ICP-OES method has relatively lower LOD and better precision when compared with those reported in the literature [12,[22][23][24]. However, the preconcentration factor for the developed was lower than those reported by Duan et al [12].…”
Section: Comparison Of Sdspme/icp-oes Methods With Other Sample Preparcontrasting
confidence: 43%
“…The comparative results are summarised in Table 5. The analytical figures of merit obtained revealed that the SDSPME/ICP-OES method has relatively lower LOD and better precision when compared with those reported in the literature [12,[22][23][24]. However, the preconcentration factor for the developed was lower than those reported by Duan et al [12].…”
Section: Comparison Of Sdspme/icp-oes Methods With Other Sample Preparcontrasting
confidence: 43%
“…The procedure used in this paper for the oxidation of the MWCNTs is described in detail in ref. 13. In this work quartz glass discs with a diameter of 30 mm and a thickness of 3 mm AE 0.1 mm were used as sample holders for introducing the sample into the TXRF instrument.…”
Section: Methodsmentioning
confidence: 99%
“…A reliable accuracy, which also agreed with published standards [19] and was calculated by recovery, was 97%. The detection limit calculated based on the sensitivity, background count rate, and continuing time was 0.06-0.20 ng/ml [50]. This method is fast, has high selectivity, and is reliable, and it possesses the possibility of sample multi-measurement Kocot and others [51] have developed a new method for the determination and speciation of selenium (Table 10) using dispersive micro solid phase extraction (DMSPE) with graphene as adsorbent coupled with energy dispersive X-ray fluorescence spectrometry (ED-XFS).…”
Section: Selenium Spme Coupled With X-ray Fluorescence and Absorptionmentioning
confidence: 99%
“…One such report involves a novel method for determination of selenite (Table 10) after chemical modification by ammonium pyrrolidine dithiocarbamate (APDC) and using dispersive solid phase microextraction (DSPME) prior to X-ray fluorescence spectrometry analysis [50]. Oxidized multi-walled carbon nanotubes (MWCNTs) were used as an adsorbent.…”
Section: Selenium Spme Coupled With X-ray Fluorescence and Absorptionmentioning
confidence: 99%